RIPPLE STUDY PRESSURE PLATE VODOBOYNUYU HYDRAULIC STRUCTURES - V. M. Ivanov; S. G. Pchelintsev; P. V. Rozhkov; S. V. Skorikov; I. A. Stoyan (Вестник Северо-Кавказского федерального университета, 2022)
The analysis of the results of experiments to determine the values of the pressure pulsations in the area vodo-boynoy plate for overflow dam at various modes soprezheniya forebay.